The Role of AI in Supporting Independent Writing: A Qualitative Case Study - Faizhal, Rahmat; Ilham, Ilham; Irwandi, Irwandi; Rahmaniah, Rima (JOLLT Journal of Languages and Language Teaching, 2025)
This qualitative descriptive case study investigates the role of Artificial Intelligence (AI) in supporting independent English writing learning at the University of Muhammadiyah Mataram. Sixteen students using AI-based tools, like Grammarly and ChatGPT, were selected via purposive sampling to provide detailed insights. Data were collected through open-ended and closed-ended questionnaires, supplemented by interviews. The findings indicate that AI tools significantly assist in grammar correction, sentence structuring, and idea generation, enhancing learners’ autonomy and confidence in writing. However, challenges such as overreliance, reduced creativity, and diminished originality underscore the importance of integrating AI thoughfully, highlighting the need for balanced integration of AI into learning processes. The study emphasizes developing pedagogical strategies that promote AI as a supplementary resource rather than a primary tool, ensuring students maintain critical thinking and creative expression. Additionally, ethical considerations were discussed, including data privacy and the potential cognitive effects of AI usage. Implications for curriculum design suggest incorporating guided AI usage and reflective writing activities to balance technological support with skill development. Future research should explore adaptive AI systems for personalized feedback and strategies to enhance writing skills without fostering dependency.